2020
DOI: 10.1038/s41598-020-73608-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects on cardiac function, remodeling and inflammation following myocardial ischemia–reperfusion injury or unreperfused myocardial infarction in hypercholesterolemic APOE*3-Leiden mice

Abstract: Many novel therapies to treat myocardial infarction (MI), yielding promising results in animal models, nowadays failed in clinical trials for several reasons. The most used animal MI model is based on permanent ligation of the left anterior descending (LAD) coronary artery in healthy mice resulting in transmural MI, while in clinical practice reperfusion is usually accomplished by primary percutaneous coronary interventions (PCI) limiting myocardial damage and inducing myocardial ischemia–reperfusion (MI-R) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“… 43 This underscores the complex interplay between different mechanisms of ischaemia and concomitant luxating cardiovascular risk factors and the necessity of selecting appropriate experimental models to investigate hypotheses correctly. 50 Following unreperfused MI, we showed that PC‐mAb therapy compared to control reduces circulating monocytes, accompanied by a reduced IS and restricted LV dilatation.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“… 43 This underscores the complex interplay between different mechanisms of ischaemia and concomitant luxating cardiovascular risk factors and the necessity of selecting appropriate experimental models to investigate hypotheses correctly. 50 Following unreperfused MI, we showed that PC‐mAb therapy compared to control reduces circulating monocytes, accompanied by a reduced IS and restricted LV dilatation.…”
Section: Discussionmentioning
confidence: 87%
“…Additionally, myocardial ischaemia‐reperfusion injury in hypercholesterolaemic APOE*3‐Leiden mice preceded by a pre‐ischaemic Ly‐6C hi monocytosis resulted in a decreased LV function as well, but was paradoxically coinciding with a reduced IS 43 . This underscores the complex interplay between different mechanisms of ischaemia and concomitant luxating cardiovascular risk factors and the necessity of selecting appropriate experimental models to investigate hypotheses correctly 50 . Following unreperfused MI, we showed that PC‐mAb therapy compared to control reduces circulating monocytes, accompanied by a reduced IS and restricted LV dilatation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Below, anti-inflammatory and immunomodulatory therapies will be briefly highlighted. In addition, the selection of an appropriate animal model to ensure optimal translation of novel cardioprotective therapies from bench-to-bedside is of the utmost importance ( 248 , 249 ), ideally allowing for an atherosclerotic phenotype and myocardial ischemia–reperfusion injury ( 250 ).…”
Section: Immunomodulatory Therapies In Clinical Practicementioning
confidence: 99%
“…A recent report indicated that TLR4 deficiency contributes to less myocardial injury and inflammatory symptoms after the induction of I/R (29). The inflammatory reaction is a key hallmark of I/R, and its modulation has been shown to be beneficial in previous investigations (30,31). Specifically, the TLR4/NF-κB signaling pathway plays a pivotal role in I/R injury, promoting a marked expression of proinflammatory cytokines in cardiomyocytes under I/R conditions (32).…”
Section: Lipopolysaccharide Activates Akt and Erk1/2 To Reduce Cardiac Fibroblast Apoptosis Induced By Simulated Ischemia/reperfusionmentioning
confidence: 99%